Management of intra-operative tracheal injuries during transhiatal esophagectomy (IMC Journal of Medical Science, 2021)
Background and objective: In transhiatal esophagectomy, iatrogenic injuries to trachea are very uncommon but when it happens it is potentially lethal and has high morbidity. This study aimed to investigate the incidence and outcome of tracheal injuries during transhiatal esophagectomy.Methods: The medical records of 608 patients who underwent transhiatal esophagectomy for esophageal cancer from January 2000 to January 2019 were analyzed.Results: Out of 608 transhiatal esophagectomy, four (0.66%) patients sustained injuries to major airway. Three injuries occurred during transhiatal and one injury during transcervical part of dissection. All the injuries occurred in trachea proximal to carina. All four injuries were closed primarily, re-enforced by muscle and fascial pledgets.Conclusion: Tracheobronchial injury is a rare complication of transhiatal esophagectomy, mostly seen in patients who receive neo-adjuvant therapy or have locally advanced growth with dense adhesions. Its immediate recognition and closure decreases the mortality and morbidity associated with this rare but fatal intra-operative complication. It can be managed effectively by primary closure, with or without muscle and fascial pledget reinforcement.Ibrahim Med. Coll. J. 2021; 15(1): 26-30